Investigation of PEMFC performance for cruising hybrid powered fixed-wing electric UAV in different temperatures - Bayrak, Zehra Ural; Kaya, Ufuk; Oksuztepe, Eyyup (Pergamon-Elsevier Science Ltd, 2020)
In this paper, the performance of the proton exchange membrane fuel cell (PEMFC) for cruising hybrid powered fixed-wing unmanned aerial vehicle (UAV) is investigated in different temperatures. The hybrid powered UAV has two power sources: FC and battery. In this regard, Lithium-Ion (Li-ion) and Nickel Metal Hydride (Ni-MH) are selected as battery types. The PEMFC performance is analysed in three scenarios determined as FC, FC & Li-ion and FC & Ni-MH. The linearized UAV model is simulated in MATLAB/Simulink and only cruise phase of flight considered. Simulation results shown that the UAV model with pure FC has the longest endurance. The endurance has influenced from total weight of the UAV and hybrid system characterization. Furthermore, temperature changes also affect fuel consumption. This paper provides a general description of the proposed UAV model with three types of hybrid power source and describes the design methods and simulation cases for long endurance. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: PEMFC; UAV; Hybrid system; Long endurance; Hydrogen consumption; PMSM